Innovative X-Ray Absorption Technology for Improved Monitoring of the Degradation and Oxidation of Granular Activated Carbon Filters Used in Hospital Water Treatment Systems - Jeamichel Puente Torres; Harold Crespo Sariol; Thayset Mariño Peacok; Tom Haeldermans; Guy Reggers; Jan Yperman; Peter Adriaensens; Robert Carleer; Dries Vandamme (C)
This study introduces a novel, non-invasive X-ray absorption analysis (XRA) method to evaluate the photonic absorption process of granular activated carbon (GAC) in hospital water purification systems. By leveraging digital radiographic images, this innovative technique monitors the deterioration and oxidation of the GAC filter, predicts its remaining lifetime, and estimates its water dechlorinating capacity. Analyzing the entire GAC filter and making a reuse possible, the new XRA method provides valuable insights into the filter’s condition, enhancing water purification efficiency and costs without analyzing subsamples. Complementary analytical techniques on subsamples, taken at various depths, did not yield valuable additional information of the GAC filter exhaustion condition, nor additionally make a reuse impossible.